A model of plant isoprene emission based on available reducing power captures responses to atmospheric CO2. Issue 1 (24th March 2014) - Morfopoulos, Catherine; Sperlich, Dominik; Peñuelas, Josep; Filella, Iolanda; Llusià, Joan; Medlyn, Belinda E.; Niinemets, Ülo; Possell, Malcolm; Sun, Zhihong; Prentice, Iain Colin
Summary We present a unifying model for isoprene emission by photosynthesizing leaves based on the hypothesis that isoprene biosynthesis depends on a balance between the supply of photosynthetic reducing power and the demands of carbon fixation. We compared the predictions from our model, as well as from two other widely used models, with measurements of isoprene emission from leaves of Populus nigra and hybrid aspen (Populus tremula × P. tremuloides) in response to changes in leaf internal CO2 concentration (Ci) and photosynthetic photon flux density (PPFD) under diverse ambient CO2 concentrations (Ca). Our model reproduces the observed changes in isoprene emissions with Ci and PPFD, and also reproduces the tendency for the fraction of fixed carbon allocated to isoprene to increase with increasing PPFD. It also provides a simple mechanism for the previously unexplained decrease in the quantum efficiency of isoprene emission with increasing Ca. Experimental and modelled results support our hypothesis. Our model can reproduce the key features of the observations and has the potential to improve process‐based modelling of isoprene emissions by land vegetation at the ecosystem and global scales.